1995
DOI: 10.1006/viro.1995.1525
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Preliminary Characterization of a Chitinase Gene in the Autographa californica Nuclear Polyhedrosis Virus Genome

Abstract: A functional chitinase gene (chiA) has been identified in the genome of the Autographa californica nuclear polyhedrosis virus (AcMNPV). It is expressed in the late phase of virus replication in insect cells. High levels of both endo- and exochitinase activity were detected by 12 hr p.i. and remained stable throughout infection. An AcMNPV chiA protein-specific antibody was prepared using recombinant material prepared in bacteria. This was used to demonstrate that a product of approximately 58 kDa was synthesise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
108
0
9

Year Published

1997
1997
2012
2012

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 131 publications
(125 citation statements)
references
References 0 publications
8
108
0
9
Order By: Relevance
“…The results indicated that the HaSNPV chitinase is a late gene. Its expression pattern was similar to that of AcMNPV (Hawtin et al, 1995).…”
Section: Transcriptional and Expressional Analysismentioning
confidence: 61%
See 2 more Smart Citations
“…The results indicated that the HaSNPV chitinase is a late gene. Its expression pattern was similar to that of AcMNPV (Hawtin et al, 1995).…”
Section: Transcriptional and Expressional Analysismentioning
confidence: 61%
“…The baculoviral chitinases identified so far are all belonging to family 18 chitinases. It was previously suggested that the AcMNPV chitinase is closely related to the chitinase of S. marcescens (Hawtin et al, 1995). Further phylogenetic analyses, however, could not confirm the proposed lateral transfer from bacteria to baculoviruses (Kang et al, 1998).…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…In addition, the dead body of a CPd-infected larva remains comparatively intact. The chitinase gene in the genome of NPVs (Hawtin et al, 1995) may fulfil a function similar to that of BmNPV-CP.…”
Section: Discussionmentioning
confidence: 99%
“…Chitinolytic enzymes are essential for chitin turnover and metabolism in chitincontaining organisms, but also exist in higher vertebrates, some plants, bacteria and baculoviruses containing no chitin compounds in relation to self-defense, nutrient assimilation and host invasion (Cohen-Kupiec and Chet, 1998;Collinge et al, 1993;Hawtin et al, 1997;Lyou et al, 2009).…”
Section: Introductionmentioning
confidence: 99%